Hospital acquired infection, evaluation of point of prevalence in a 147 beds italian hospital. (13th November 2019) - Gori, F; Vonci, N; Santoriello, G; Quercioli, C; Messina, G; Sancasciani, S
Abstract: Background: Hospital Acquired Infections (HAI) have become a public health priority worldwide, leading to higher medical costs, prolonged hospital stays, and increased mortality. The point of prevalence analysis (PPA) of HAI and antibiotics (ATB) consumption is extremely relevant for its social and economic impact. Aim of this study is to evaluate the prevalence of HAI and to analyze ATB consumption in 147 beds hospital. Material and Methods: This prevalence study was conduced on March 23, 2018, we analyzed the clinical documentation of 78 patients hospitalized in the Hospital of Val D'Elsa, Siena, Italy and searched for evidence of HAI and for all indication of ATB therapy in all hospital wards. HAI were defined according to guidelines of European Centers for Disease Control and Prevention (ECDC 4.2) using Stata 12. Results: We analyzed a total of 78 patients (51, 3% female), average age was 71, 6 (sd ± 23, 4) years, mean lenght of stay 7, 2 (sd ± 7, 9) days. Patients included in the study were recovered mostly in General Medicine ward (62, 8%); 23% of patients underwent surgery. Fifty-one point three of patients had Peripheral Venous Catheter, 17, 9% Central Venous Catheter and 47, 4% Urinary Catheter. Three infections were discovered (PPA 3, 8%); 2 HAIs were found in Medicine ward, the third one in the Intensive Care Unit. The chi-square test did not show statistically significant differences with the last year's results in the same wards (p = 0.3305). Fifty-four percent of all patients received ATB, the most used class were third generation Cephalosporines (50%), followed by Carbapenems (19%) and Fluoroquinolones (7%). Conclusions: PPA of HAI was 3, 8%, comparable to last year's (3, 5%). This is a positive result when compared to regional and national point prevalence study realized by ECDC in 2012 (6, 2% in Tuscany Region, 6% in Italy). Our analysis showed that ATB consumption was quite high: and it is in agreement with those provided by the Tuscany Region. Key messages: in our hospital we report an excellent result about the pint of prevalence of hospital acquired infections 3, 8%. The antibiotics consumption in our hospital is quite high, the most frequently used antibiotic class is the third generation Cephalosporines.